Синкретизм у матеріальній культурі населення Буковини ХІІ – першої половини ХІІІ ст. - Возний, Ігор (Релігія та Соціум. – Чернівці: Чернівецький національний університет, 2019)
Igor Vozny SYNCRETISM IN THE MATERIAL CULTURE OF THE POPULATION OF THE BOOK OF XII - THE FIRST HALF OF ХІІІ ST. The article deals with issues related to the spread of Christianity into the territory of Bukovina and the remnants of ezicism, which existed there up to the 15 th century. Some pagan traditions have survived to this day. Archeological materials testify that after the adoption of Christianity, domestic beliefs, representing a range of primitive views, customs and ordinances that have come from ancient times, slowly retreat under the pressure of a new faith. This evidence is observed on the example of the ancient Jewish rite of the "building sacrifice", which was certified in the butterfly of the White Stone Church in the Vasilev chronicle, in the foundation of the residence of the feudal lord at the Chornovsky settlement. It is proved that the so-called "building sacrifice" is connected with the domestic outlook, which was based on the idea of the need for a victim in the construction of any building to ensure its strength, to protect the inhabitants from the influence of "evil spirits". It is substantiated that the important role of the amulets, which had to distract a person from "unclean power" and protect the exposed parts of the body. By the way they were worn, one could distinguish headgear, neck, breast pins, hand decorations and belts. The Slavs had a sufficiently developed cult of the sun, whose solar symbol embraced a variety of nap rings, glass and metal lamellae and wicker bracelets. Amulets had a magical meaning, performed breast and belt acne. Important protections that were widely used in magic actions when protected from impact, fire or burial ceremonial activity were so-called "thunder arrows". Pagan symbolism has survived on many household objects, found among the ancient antiquities of the region. Thus, the archaeological materials obtained during the studies on the territory of Bukovina allow us to conclude that the Orthodox-pagan complex, which was historically in the process of Christianization of Rus and penetrated the world history of the Slavs, represented a complex, confusing circle of beliefs, customs, prejudices, religions, mystic rites, and rituals of the native period, which merged with the elements of Orthodoxy
Keywords: syncretism; double faith,; «buiding sacrifice»,; temporal rings,; diadem; lunnica,; «thunder arrows»,; cult of mirror